Design of AXI4-Stream based Modulator IP Core for Visible Light Communication System-on-Chip - Erwin Setiawan; Trio Adiono (JURNAL INFOTEL, 2018)
In this paper, the design of AXI4-Stream based modulator IP core for Visible Light Communication is reported. The modulator IP core conforms to the AXI4-Stream protocol standard, which is widely used in System-on-Chip (SoC) design. There are three modulation types in this IP core namely, Binary Phase Shift Keying (BPSK), Quadrature Phase Shift Keying (QPSK), and Quadrature Amplitude Modulation-16 (QAM-16). These modulation types are commonly used in the DCO-OFDM system. The modulation types can be selected programmatically from software that runs in the main processor by accessing the control register. The output of the modulator is designed for DCO-OFDM modulation using 64-point IFFT. According to the simulation results, this modulator IP core can achieve a throughput of 95.36 Mb/s, 184.77 Mb/s, and 347.81 Mb/s for BPSK, QPSK, and QAM-16, respectively. This modulator IP core is reusable in the DCO-OFDM system, so it increases productivity in DCO-OFDM system design.